Ibn Taymiyyah’s position on the distortion of the wording of the Torah and the Gospel (Arabic) - Ali Matooq Altamimi, Abdulla; Shehu, Fatmir (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2022)
This scientific paper will clarify the position of Shaikh al-Islam Ibn Taymiyyah (may Allah Almighty have mercy on him), towards an issue of great importance that was stipulated in al- Qur’ān and as-Sunnah, and scholars dealt with it in their studies and research, which is the issue of distortion of the wording of the Torah and the Gospel. By the explanation, the position presented in this message distinguishes from other positions contrary to it. As the position of those who say that the wording of the Torah and the Gospel has not been subjected to change and alteration, this study will include an explanation of the evidence that Ibn Taymiyyah relied on. This study seeks to clarify the position and the evidence of one of those who believe in the partial distortion of the Torah and the Gospel and to show how to deal with distorted books. Its importance in terms of attaching the position of those who assert partial distortion including Ibn Taymiyyah with al-Qur’ān and as-Sunnah is an issue that has its place in the Islamic Legal Sources. In other words, the research will reveal previous scholars' approaches in dealing with or judging the holy books mentioned in al-Qur’ān. This paper discusses, firstly: the terms to be comprehended in this research, such as the literal and technical meaning of distortion, and the definition of the Torah and the Gospel, after introducing Shaikh al-Islam Ibn Taymiyyah (may Allah Almighty have mercy on him); secondly: the explanation of the scholarly position on distortion in general, i.e., verbal distortion and moral distortion, and then the explanation of the position of those who say that there is partial distortion in the text; and thirdly: the evidence on which Ibn Taymiyyah relied. The approach used in this study is descriptive-analytical, where the description of Sheikh of Islam’s position towards the distortion of the Torah and the Bible, and the explanation of his saying about the rational and traditional proofs.